A theoretical and experimental evaluation of an internally and externally finned refrigerant-12 condenser. - De Villiers, Pieter Kuyper (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1977.